2021
DOI: 10.1177/10497323211011589
|View full text |Cite
|
Sign up to set email alerts
|

Collective Emotion During Collective Trauma: A Metaphor Analysis of the COVID-19 Pandemic

Abstract: This study provides insight into lived experiences of the COVID-19 pandemic in the United States. Participant metaphors of the pandemic were collected by conducting in-depth semi-structured interviews ( N = 44). Participants were asked to compare the pandemic with an animal and with a color, and to provide contextual sensemaking about their metaphors. A metaphor analysis revealed four convergent mental models of participants’ pandemic experiences (i.e., uncertainty, danger, grotesque, and misery) as well as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 54 publications
(85 reference statements)
0
53
0
5
Order By: Relevance
“…Collective trauma is a group-level cataclysmic event that strikes at the basic fabric of society ( Hirschberger, 2018 ). In the COVID-19 pandemic, individuals have faced multiple traumas, such as unemployment, isolation, and death, and the entire society has suffered from economic recession and a loss of population and resources ( Barbosa et al, 2021 ; Stanley et al, 2021 ). It is indisputable that the COVID-19 pandemic has become a collective trauma ( Holman & Grisham, 2020 ; Masiero et al, 2020 ).…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
“…Collective trauma is a group-level cataclysmic event that strikes at the basic fabric of society ( Hirschberger, 2018 ). In the COVID-19 pandemic, individuals have faced multiple traumas, such as unemployment, isolation, and death, and the entire society has suffered from economic recession and a loss of population and resources ( Barbosa et al, 2021 ; Stanley et al, 2021 ). It is indisputable that the COVID-19 pandemic has become a collective trauma ( Holman & Grisham, 2020 ; Masiero et al, 2020 ).…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
“…Previous research has shown that a wide variety of metaphors have been used in communication about the COVID-19 pandemic in the context of news discourse, political discourse and online writing. To date, however, very little empirical research has been conducted to address how metaphors are facilitated in people’s narratives of their lived experiences during the COVID-19 crisis (e.g., [ 26 ]). Notably, Stanley et al [ 26 ] conducted in-depth semi-structured interviews with 44 American individuals.…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, very little empirical research has been conducted to address how metaphors are facilitated in people’s narratives of their lived experiences during the COVID-19 crisis (e.g., [ 26 ]). Notably, Stanley et al [ 26 ] conducted in-depth semi-structured interviews with 44 American individuals. Participants were asked to compare the COVID-19 pandemic with an animal and a color, and to explain their metaphors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because metaphors allow for a detailed and nuanced knowledge of a person’s experience, we believe they represent a relevant avenue to derive a better understanding of the lived experience of bereavement during the COVID-19 pandemic. Recently, Stanley et al ( 2021 ) conducted a metaphor analysis of the COVID-19 pandemic and provided insight into peoples’ collective trauma. Their qualitative study suggests that individuals can articulate deep implicit emotions about their pandemic experiences by sharing and reflecting on metaphors related to the traumatic events.…”
Section: Introductionmentioning
confidence: 99%